Research on financial risk management and control of agricultural products supply chain—A case study of Jiangsu Province of China - Yang, Jing; Tang, Decai; Kong, Haojia; Boamah, Valentina (Frontiers in Environmental Science, 2022)
The rapid development of agriculture is inseparable from the strong support of agricultural supply chain finance. The core problem of agricultural supply chain finance is managing and controlling agricultural supply chain financial risk. Based on the identification of financial risk categories of agricultural products supply chain, this paper constructs the financial risk evaluation index system for agricultural products supply chain. It takes Jiangsu Province of China as the research object to construct the structural equation model. In this paper, the Amos method, which can analyze multiple variables simultaneously, is used to calculate the model. This paper finds that the impact levels of financial risks of the agricultural products supply chain in Jiangsu Province are from high to low: agricultural products pledge risk, credit risk, supply chain operation risk, technical risk, legal risk, and policy risk. It further puts forward countermeasures and suggestions for risk management and control from the aspects of agricultural products pledge, supply chain composition, early warning mechanism, system, and law, to play a theoretical guiding role in the effective development of agricultural products supply chain financial business in Jiangsu Province. Finally, it promotes the integrated development of the agriculture, finance, and circulation industry in Jiangsu Province and the whole country.